Peningkatan Kapasitas Produksi Gula Semut Menggunakan Teknologi Tepat Guna Pada Home Industri di Desa Sriwijaya - Agus Putra AS; Afrah Junita; Nursamsu Nursamsu (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The purpose of this service activity is to provide appropriate technological tools to the home industry group in processing sugar cane water into ant sugar and provide knowledge to the community in processing sugar cane water into ant sugar. This service activity will later be given to the people of Sriwijaya Village, Kuala Simpang District, Aceh Tamiang Regency. So far, the home industry group uses manual tools so that it produces low quality ant sugar. The existence of appropriate technology machines will provide changes in processing in producing quality and clean ant sugar to be marketed. Appropriate technology machines are expected to produce more granulated sugar than before than using manual machines. This service activity has a positive impact on the home industry and the community in processing and producing ant sugar by using appropriate technological tools.